Tyrosine Kinases in Autoimmune and Inflammatory Skin Diseases - Szilveszter, Kata P.; Németh, Tamás; Mócsai, Attila (Frontiers in Immunology, 2019)
Tyrosine kinases relay signals from diverse leukocyte antigen receptors, innate immune receptors and cytokine receptors, and therefore mediate the recruitment and activation of various leukocyte populations. Non-receptor tyrosine kinases of the Jak, Src, Syk and Btk families play major roles in various immune-mediated disorders, and small-molecule tyrosine kinase inhibitors are emerging novel therapeutics in a number of those diseases. Autoimmune and inflammatory skin diseases represent a broad spectrum of immune-mediated diseases. Genetic and pharmacological studies in humans and mice support the role of tyrosine kinases in several inflammatory skin diseases. Atopic dermatitis and psoriasis is characterized by an inflammatory microenvironment which activates cytokine receptors coupled to the Jak-Stat signaling pathway. Jak kinases are also implicated alopecia areata and vitiligo, skin disorders mediated by cytotoxic T lymphocytes. Genetic studies indicate a critical role for Src-family kinases and Syk in animal models of autoantibody-mediated blistering skin diseases. Here we review the various tyrosine kinase signaling pathways and their role in various autoimmune and inflammatory skin diseases. Special emphasis will be placed on identification of potential therapeutic targets, as well as on ongoing preclinical and clinical studies for the treatment of inflammatory skin diseases by small-molecule tyrosine kinase inhibitors.